Embodied Learning: Why at School the Mind Needs the Body - Macedonia, Manuela (Frontiers in Psychology, 2019)
Despite all methodological efforts made in the last three decades, Western instruction grounds on traditional principles. Most educational programs follow theories that are mentalistic, i.e., they separate the mind from the body. At school, learners sit, watch, listen, and write. The aim of this paper is to present embodied learning as an alternative to mentalistic education. Similarly, this paper wants to describe embodied learning from a neuroscientific perspective. After a brief historical overview, I will review studies highlighting the behavioral effectiveness of embodied instruction in second language learning, mathematics and spatial thinking. On this base, I will discuss some of the brain mechanisms driving embodied learning and describe its advantages, clearly pleading in favour of instructional practice that reunites body and mind.